Single Port Laparoscopic Liver Resection for Hepatocellular Carcinoma: A Preliminary Report - Stephen Kin Yong Chang; Maria Mayasari; Iyer Shridhar Ganpathi; Victor Lee Tswen Wen; Krishnakumar Madhavan (International Journal of Hepatology)
Single port laparoscopic surgery is an emerging technique, now commonly used in cholecystectomy. The experience of using this technique in liver resection for hepatocellular carcinoma is described in a series of 3 cases with single port laparoscopic liver resection performed during 2010. All patients were male aged 61 to 70 years, with several comorbidities. There were no complications in this early series. The length of hospital stay was 3–5 days. The blood loss was 200–450 mL, with operating time between 142 and 171 minutes. We conclude that this technique is feasible and safe to perform in experienced centers.